Canine prostate: would the dog be an important model for the study of new drugs? - Alves, Carlos Eduardo Fonseca [UNESP]; Vicente, Igor Simões Tiagua [UNESP]; Calazans, Sabryna Gouveia [UNESP]; Amorim, Renée Laufer [UNESP] (Science Alert, 2013)
Prostate cancer is ranked as the second leading cause of cancer-related death in men aged above 50 years and the long-term survival of patients with metastatic disease has not changed significantly. This fact is related mainly to the limited therapeutic options available. Despite numerous studies on PCa in humans, succes was not obtained in clinical trials of targeted therapies because of the difficulty in standardizing an ideal animal model for application in clinical trials. The use of dogs as a model for the clinical trials of new drugs can bring in higher accuracy in assessing the response of tumors to the drugs tested, with the assumption that the dog is a natural model of the disease and shares the same environment as humans. Due to the importance of prostate carcinoma in man the goal of the review is to identify the strengths of the dog as a model fot the development of new therapy for prostatic carcinoma.
Keywords: Animal model; Clinical trial; Men; Prostatic carcinoma